Resin matrix ceramics – mechanical, aesthetic and biological properties - ALVES DE LUCENA,Mariana (2021)
ABSTRACT Resin matrix ceramics consist in a polymeric matrix with predominantly inorganic refractory compounds which may include porcelain, glass, ceramics, and glass ceramics, and are divided into three subgroups: Nanoceramics, Vitroceramics, and Zirconia-silica. The aim of this study was to compare, through a literature review, the mechanical and biological properties of resin matrix ceramics, with glass matrix ceramics and polycrystalline ceramics. After reviewing 44 articles found in the US National Library of Medicine (PubMed) database (studies published in English, human clinical studies, in vitro or in vivo studies) that evaluated some properties of this material, such as elasticity modulus, wear resistance, adhesiveness, stain resistance and hardness, this article concluded that, although they belong to the same group, resin matrix ceramics are different from each other due to their microstructures. Moreover, when compared to other ceramic groups, it showed some superior properties, such as flexural strength, fatigue strength and internal adaptation.